CONTROL OF THE ELECTRIC FIELD OF DIELECTRIC SEPARATING DEVICES BY THE SUPERIMPOSITION METHOD - Bakhodir Djurakhanovich Mamadzhanov; Shukhratbek Soyibjon ugli Mannobboev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article discusses the easy control and calculation of electric fields generated by a system of grid electrodes of dielectric sorters by the method of superposition.